The SAGE handbook of diplomacy - Constantinou, Costas M. 1965-; Kerr, Pauline; Sharp, Paul 1953- (SAGE, 2016)
'The SAGE Handbook of Diplomacy' provides a major thematic overview of diplomacy and its study that is theoretically and historically informed and in sync with the current and future needs of diplomatic practice